They will beat the memory out of us: forcing nonviolence on forgetful movements - Gelderloos, Peter (Pluto Press, 2024)
"In the face of ecological crisis, police repression and white supremacy, there is an apparent lack of options for effective resistance. Here, Peter Gelderloos brings to life some of the conflictive and subversive events of the last couple of decades in a radical new criticism of nonviolence. The book weaves history, vignettes, interviews and personal reflections to show how our movements suffer from an inability to pass on lessons learned from one generation to the next. Learning from the antiracist rebellions triggered by police murders from Minneapolis to Bristol, and the climate campaigns that often fail to centre an anticolonial consciousness, we can understand nonviolence as a symptom of social amnesia, an inability to remember our places in this world and what we have learned from past episodes of resistance. Cautioning against future waves of pacification and forgetting, this book urges us to collectivise memory and develop the methods we need to fight for our survival." -- Publisher description